LEARNING MATERIALS HAND CRAFT OF CLAY POWDER FOR CLASS VIII SMPN 3 ANGGERAJA ENREKANG - Mardhathillah Ayu Katu; Abd Aziz Ahmad; Benny Subiantoro (Universitas Negeri makassar, 2019)
This research is a survey research with a qualitative descriptive level, which aims to describe the learning of handicrafts from clay flour for students of class VIII SMP 3 Anggeraja. The objective of this research is learning handicrafts from clay flour, the source of the data in this study are teachers and students of class VIII. Data collection techniques in this study through observation, interviews, and documentation. Data analysis techniques in this study used qualitative descriptive analysis techniques. Based on the results of research on handicraft learning from clay flour for eighth grade students of SMP 3 Anggeraja through several stages, namely the learning planning stage at this stage the teacher prepares learning tools (RPP), learning materials, products and craft drawings from flour clay, as well as tools and the material that will be used by the teacher during the learning, then the implementation stage of learning carried out in class VIII-B with 3 meetings, the first meeting of material giving, the second meeting of the practice of making clay flour, the third meeting, the finishing stage and the suggestion, as a whole has been in accordance with the RPP made by the teacher. The next stage is the assessment stage, at this stage the teacher assesses student performance results based on 4 aspects, namely preparation of tools and materials with a weight of 30%, ideas/ideas with a weight of 20%, creativity with a weight of 30%, and finishing with a weight of 20%. Based on the overall assessment results of grade VIII-B students, it has been declared successful in carrying out the learning process because it has reached the value of the predetermined KKM standard, which is 78.